EVALUASI PROGRAM SEKOLAH SEHAT TINGKAT SEKOLAH DASAR DI KABUPATEN KUTAI TIMUR - Septian Fernandy; Muhammad Noor; Erwin Resmawan (Jurnal Administrative Reform, 2021)
This study aims to describe the results of the assessment of the implementation of the Healthy School Program at Elementary School Level in East Kutai Regency. This type of research is descriptive qualitative. Data collection techniques by means of interviews, observation, and documentation. Data analysis using an interactive analysis model. The results show that the evaluation of the Healthy School Program shows that in general it has not been maximized where from various criteria, namely effectiveness related to goal achievement, efficiency related to the use of resources both money and human resources, equity related to benefits and financing that are distributed evenly, accuracy is related to the achievement of goals, responsiveness related to the school's response to the program, and adequacy related to the results achieved. Only one school, namely SD Negeri 010 Sangatta Utara, has been achieved while the other two schools are still unable to implement the whole thing, such as being constrained by budget, health teachers and infrastructure advice.Keywords: Evaluation, Healthy School Program.